1998
DOI: 10.1002/(sici)1097-0185(199806)251:2<245::aid-ar14>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mitosis in binucleated and mononucleated newt cardiac myocytes

Abstract: Background: The cultured adult newt ventricular myocyte has been shown to undergo mitosis and cytokinesis in a fully differentiated state. Insight into its proliferation and cellular changes during the repair process involves obtaining a better understanding of the nuclear pattern (mononucle-ated, binucleated, or multinucleated) resulting from mitotic events. Mitosis is easily observable in cultured newt cardiac myocytes using phase-contrast microscopy. Methods: From days 8-19 in culture, the process of mitosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 34 publications
(37 reference statements)
1
17
0
1
Order By: Relevance
“…36 The same has been observed in adult newt cardiomyocytes. 18,37 However, our study has demonstrated neither adult cardiomyocyte proliferation in vivo nor its relevance after myocardial injury.…”
Section: Can Adult Mammalian Cardiomyocytes Proliferate?mentioning
confidence: 61%
“…36 The same has been observed in adult newt cardiomyocytes. 18,37 However, our study has demonstrated neither adult cardiomyocyte proliferation in vivo nor its relevance after myocardial injury.…”
Section: Can Adult Mammalian Cardiomyocytes Proliferate?mentioning
confidence: 61%
“…However, while restricted cell cycle reentry may occur in the injured human versus mouse hearts [1-4% (13) human vs. 0.0014% mouse (210) cardiac myocytes], the ultimate fate of these myocytes and whether species-specific differences really exist with respect to proliferative capacity remain unresolved. In contrast, in species such as newt where consensus exists on the capacity for myocardial regeneration, it has been demonstrated that mononucleated myocytes were more likely to successfully undergo cytokinesis than binucleated myocytes (150). When binucleated newt myocytes enter the cell cycle, it resulted in variably nucleated myocytes in the majority of cases as opposed to cytokinesis.…”
Section: A Adult Cardiac Myocytes Are Terminally Differentiatedmentioning
confidence: 98%
“…By contrast, this degree of binucleation is not seen in zebrafish; ∼95% of cardiomyocytes in the adult zebrafish heart are mononucleated (Wills et al, 2008). Findings in newts suggest that mononucleated cardiomyocytes are more likely to undergo cytokinesis than their binucleated counterparts (Matz et al, 1998). This tendency appears to hold true in mammals: in their examination of the effect of Nrg1/ErbB4 signaling on adult mouse cardiomyocytes, Bersell et al noted that mononuclear cells were more likely to undergo both karyokinesis and cytokinesis after Nrg1 treatment in vitro and in vivo (Bersell et al, 2009).…”
Section: Early Postnatal Binucleation and Endoreplication In Mammalsmentioning
confidence: 99%